2011
DOI: 10.1186/1476-069x-10-67
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution from traffic and cancer incidence: a Danish cohort study

Abstract: BackgroundVehicle engine exhaust includes ultrafine particles with a large surface area and containing absorbed polycyclic aromatic hydrocarbons, transition metals and other substances. Ultrafine particles and soluble chemicals can be transported from the airways to other organs, such as the liver, kidneys, and brain. Our aim was to investigate whether air pollution from traffic is associated with risk for other cancers than lung cancer.MethodsWe followed up 54,304 participants in the Danish Diet Cancer and He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
180
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 170 publications
(197 citation statements)
references
References 55 publications
12
180
5
Order By: Relevance
“…75 A maximum density of B2 molecules of HNO 3 nm À2 TiO 2 was reported. 74 With the maximum amount of oxidized NO found during this work (n rem = 9.25 Â 10 À6 mol) and the geometric surface area of the sample a maximum density of B1 molecule of HNO 3 per 1000 nm 2 is calculated to be produced during a single experimental run performed in this work indicating that the TiO 2 surface is far from being saturated by adsorbed HNO 3 . It is therefore suggested that a dynamic equilibrium between NO, HNO 2 /NO 2 À , and NO 2 is established comprising surface reactions as well as adsorption-desorption equilibria, but that the final oxidation product is continuously accumulated on the photocatalyst surface during the entire experimental run, thus blocking the NO adsorption sites.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…75 A maximum density of B2 molecules of HNO 3 nm À2 TiO 2 was reported. 74 With the maximum amount of oxidized NO found during this work (n rem = 9.25 Â 10 À6 mol) and the geometric surface area of the sample a maximum density of B1 molecule of HNO 3 per 1000 nm 2 is calculated to be produced during a single experimental run performed in this work indicating that the TiO 2 surface is far from being saturated by adsorbed HNO 3 . It is therefore suggested that a dynamic equilibrium between NO, HNO 2 /NO 2 À , and NO 2 is established comprising surface reactions as well as adsorption-desorption equilibria, but that the final oxidation product is continuously accumulated on the photocatalyst surface during the entire experimental run, thus blocking the NO adsorption sites.…”
Section: Discussionmentioning
confidence: 66%
“…In both photocatalytic oxidation pathways outlined in Tables 2 and 3 three holes are required to produce the species oxidizing NO to its final reaction product HNO 3 /NO 3 À , and molecular oxygen is assumed to be the principal acceptor for the conduction band electrons generated by the excitation of the TiO 2 photocatalyst. The results obtained while varying the O 2 concentration in the gas phase (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term exposure to air pollution PM increases the risk of lung cancer, respiratory diseases and arteriosclerosis, whereas short-term exposure can exacerbate several forms of respiratory diseases, i.e. bronchitis and asthma, and changes in heart rate variability (Dominici et al 2007 ;Peacock et al 2011 ;Pope et al 2009 ;Raaschou-Nielsen et al 2011 ;Rusconi et al 2011 ). However, fundamental uncertainties still exist with respect to the underlying mechanisms of toxicity that are responsible for the mortality or morbidity increases following exposure to current levels of air pollution PM (Schwarze et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the study areas were large cities and the surrounding suburban or rural communities, as specified in the online appendix (pp. [4][5][6][7][8][9][10][11][12][13]. A pooled analysis of all cohort data was not possible due to data-transfer and privacy issues but data from the four Stockholm cohorts (SNAC-K, SALT, 60-y/IMPROVE and SDPP) were pooled, and analysed and denoted as one Similarly, data from the two cohorts from the Netherlands (EPIC-MORGEN and EPIC-PROSPECT) were pooled, analysed and denoted as one [EPIC-NL].…”
Section: Design and Participantsmentioning
confidence: 99%
“…Several studies of occupational groups, such as transport workers, drivers, policemen, metal foundry workers, and gasoline service station workers exposed to gasoline vapors, engine exhaust, polycyclic aromatic hydrocarbons, and other air pollutants, have indicated weakly increased risk for kidney cancer [6][7][8] , although the literature is neither consistent 9 nor conclusive 10 . Garcia-Perez et al found higher kidney cancer mortality in Spanish general populations exposed to ambient air pollution from incinerators and hazardous waste treatment plants 11 and a cohort study of a general Danish population found positive but statistically insignificant associations between nitrogen oxides (NO x ) at the residence and kidney cancer incidence but no association with amount of street traffic near the residence 12 . Further, ultrafine particles can translocate from the airways to the kidney and other organs of experimental animals 13 and experiments have shown that diesel particles can induce cancer-relevant processes in the kidneys 14,15 .…”
Section: Introductionmentioning
confidence: 99%